2019
DOI: 10.3389/fphar.2019.01031
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Information in Summaries of Product Characteristics (SmPCs) on the Use of a Medicine in Patients With Hepatic Impairment

Abstract: Background: In 2005, the European Medicines Agency (EMA) released guidance on pharmacokinetic studies in patients with hepatic impairment. This guidance describes the design of these studies and what information should be presented in the Summary of Product Characteristics (SmPC). We aim to evaluate the availability and clinical applicability of information on medicine use in patients with hepatic impairment in SmPCs and registrational dossiers of recently approved medicines. Methods: We reviewed SmPC informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…The primary information about alterations in the pharmacology of medicines in patients with cirrhosis originates from the pre-marketing PK studies conducted by the pharmaceutical industry. In a recent article, we demonstrated that a large proportion of product labels from recently authorized medicines contained information on use in hepatic impairment patients [134]. However, we also showed that this information was frequently ambiguously formulated and therefore not per se clinically applicable.…”
Section: Further Research Topicsmentioning
confidence: 79%
See 1 more Smart Citation
“…The primary information about alterations in the pharmacology of medicines in patients with cirrhosis originates from the pre-marketing PK studies conducted by the pharmaceutical industry. In a recent article, we demonstrated that a large proportion of product labels from recently authorized medicines contained information on use in hepatic impairment patients [134]. However, we also showed that this information was frequently ambiguously formulated and therefore not per se clinically applicable.…”
Section: Further Research Topicsmentioning
confidence: 79%
“…Both guidelines do acknowledge that the effect of medicines could also be different in hepatic impairment and advise to include efficacy and safety endpoints in the PK studies when possible [29,30]. Yet, this is limited by the common design of these PK studies: a small number of patients (usually around six per severity class and often no patients with severe cirrhosis) and only a single dose of the study drug is administered [134]. Toxicological effects could be hard to detect because of a low frequency or because they resemble the natural course of cirrhosis [135].…”
Section: Further Research Topicsmentioning
confidence: 99%
“…However, safety advice and dosing recommendations in these product information summaries on medication use in patients with hepatic impairment have historically been unavailable or ambiguous. ( 59,60 ) Dedicated studies to assess the impact of hepatic impairment on PK are heterogeneous, and study reports often poorly discriminate between type and severity of CLD. ( 59 ) Therefore, many nonspecialist health care professionals are uncertain about dose adjustments and relative contraindications for people with hepatic impairment.…”
Section: Patient‐related Factorsmentioning
confidence: 99%
“…Notably, others have criticized the clinical applicability of information provided per FDA or EMA guidance for patients with cancer and hepatic impairment within the prescribing information (in the United States) and summaries of product characteristics (SmPCs; in Europe). 9 , 10 …”
Section: Introductionmentioning
confidence: 99%